Physical and Chemical Characteristics of Teak (Tectona Grandis) Leaves as Food Packaging Material - Swastika Dewi; Supriyadi Supriyadi; Umar Santoso (Indonesian Food and Nutrition Progress, 2020)
Teak (Tectona grandis) leaves is commonly used as the packaging material of traditional food in Indonesia. This study aimed to determine the physical and chemical characteristics of teak leaves with various maturation stages to obtain information about the potency of teak leaves as active packaging material. The physical characteristics analysis including leaf color, thickness, and tensile strength, while chemical characteristics were moisture, fat content, fatty acid, and volatile profile. The results showed that the color, thickness, tensile strength, moisture, and fat content, were light green, 0.306±0.024 mm, 0.22±0.114 MPa, 74.93%, and 2.52% respectively for young teak leaves; while the mature has darker green, 0.388±0.001  mm, 0.36±0.163 MPa, 73.05%, and 2.54% respectively. The fatty acid profiles showed that young teak leaves contained 5 types of fatty acids, dominated by lignoceric acid; while mature teak leaves contained 9 types of fatty acids dominated by tricosanoic acid. The volatile components of young teak leaves e.g. acid and ester compounds, while the mature was dominated by acid and ether compounds. From the results, it is suggested that the use of teak leaves as active food packaging material can be scientifically justified.